Republic of Poland : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper examines the driving factors for the broad movements of investment over the past decade in Poland. After booming for half a decade, Poland's investment plummeted during 2001-03 and has recovered only marginally since then. The paper provides a historical perspective on the evolution of economywide and sectoral investment in Poland, and briefly summarizes possible determinants of investment. It analyzes the determinants of investment more systematically using panel regressions based on sectoral data, and reports the results of in-sample and out-of-sample simulations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet